Spirituality and nursing: an Ismaili perspective on holistic nursing care - Dhamani, Khairunnisa Aziz (Journal of holistic nursing, 2014)
This article seeks to describe a professional, personal, and cultural understanding of spirituality in nursing care. It revisits and refines the many concept clarifications of spirituality in our practice discipline, while reflecting on the potential meanings and learnings from Ismaili tenets and principles within a personal nursing practice. Through a review of mainstream literature in conjunction with nontraditional literature, the implicit is made explicit in terms of similarities and differences, as well as opportunities for further exploration. The summary brings forward the persistent gaps and questions on critical areas such as creating the "place" and "operationalizing" of spirituality. These continue to challenge and intrigue nurses seeking spiritual comfort for both themselves and their clients.